BIOMASS INTO FUEL & CHEMICAL DERIVATIVES - Roshanida A. Rahman, editor; Norzita Ngadi, editor; Ahmad Kamil Hakimien Nor Aslan, contributor; Khairul Aswad Abdul Wahab, contributor; Mohd. Asmadi, contributor; Mohd. Danial Muhd. Ali, contributor; Mohd. Khairil Johari, contributor; Nik Azmi Nik Mahmood, contributor; Noor Amirah Abdul Halim, 1989-, contributor; Nor Azah Ramli, contributor; Norzita Ngadi, contributor; Nurul Saadiah Lani, 1988-, contributor; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2016)
Includes bibliographical references and index